2017
DOI: 10.1021/acs.bioconjchem.7b00648
|View full text |Cite
|
Sign up to set email alerts
|

a-Factor Analogues Containing Alkyne- and Azide-Functionalized Isoprenoids Are Efficiently Enzymatically Processed and Retain Wild-Type Bioactivity

Abstract: Protein prenylation is a post-translational modification that involves the addition of one or two isoprenoid groups to the C-terminus of selected proteins using either farnesyl diphosphate or geranylgeranyl diphosphate. Three crucial enzymatic steps are involved in the processing of prenylated proteins to yield the final mature product. The farnesylated dodecapeptide, a-factor, is particularly useful for studies of protein prenylation because it requires the identical three-step process to generate the same C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…12 peptides had undergone C-terminal hydrolytic cleavage generating a prenylated C-terminal cysteine, a further 4 peptides were cleaved and methylated, and the remaining 10 featured unprocessed C-termini (Supplementary Data 4). These findings demonstrate that YnF and YnGG labeling is compatible with endogenous post-prenylation processing by Ras-converting enzyme 1 (RCE1) and Isoprenylcysteine carboxyl methyltransferase (ICMT)28. Interestingly, we also found strong evidence for novel C-terminal processing of geranylgeranylated RAB3B, RAB3D, and RAB7A, in which the two terminal amino acids of the canonical XCXC motif have been removed (Supplementary Figure 10).…”
Section: Resultssupporting
confidence: 57%
“…12 peptides had undergone C-terminal hydrolytic cleavage generating a prenylated C-terminal cysteine, a further 4 peptides were cleaved and methylated, and the remaining 10 featured unprocessed C-termini (Supplementary Data 4). These findings demonstrate that YnF and YnGG labeling is compatible with endogenous post-prenylation processing by Ras-converting enzyme 1 (RCE1) and Isoprenylcysteine carboxyl methyltransferase (ICMT)28. Interestingly, we also found strong evidence for novel C-terminal processing of geranylgeranylated RAB3B, RAB3D, and RAB7A, in which the two terminal amino acids of the canonical XCXC motif have been removed (Supplementary Figure 10).…”
Section: Resultssupporting
confidence: 57%
“…Suppression of the pool of native isoprenoids using statins may allow C15AlkOPP to more effectively compete for labeling of those more difficult to farnesylate with potentially lower native abundances. It is also important to note that the use of this probe does not necessarily impact the function of labeled substrates as previously described 52 . Therefore, this isoprenoid tagging approach may operate in viable cells with minimal perturbations in the physiological function of prenylated proteins.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it has been demonstrated that a-factor, a farnesylated pheromone from yeast retains full activity when the farnesyl group is substituted with several chemically modified isoprenoids used for metabolic labeling. Those results suggest that such probes can be used without concern that they will cause undesired interference in normal cell physiology (Diaz-Rodriguez et al, 2017). …”
Section: Introductionmentioning
confidence: 99%